Homogeneous pressure-transmitting pyrophyllite block and preparation method thereof
By optimizing the composition and process flow of raw materials, homogeneous pressure-transfer wax stones were prepared, which solved the problem that wax stones could not effectively increase internal pressure during high-pressure synthesis in the prior art, and achieved the production of higher-quality polycrystalline diamond composite sheets and a more efficient drilling process.
Patent Information
- Application Number
- CN202411510510.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-25
AI Technical Summary
The existing sealed pressure-transfer medium purpurite cannot effectively increase the internal pressure during high-pressure synthesis, resulting in large production losses and uneven pressure transmission, increasing the risk of firefighting.
By optimizing the composition and process flow of raw materials, homogeneous pressure transfer worm stone blocks are prepared by mixing different particle sizes with additives such as water glass or porous magnesium oxide.
The production of higher-quality polycrystalline diamond composite sheets has been achieved, reducing the cracking and breaking of drill teeth during the rotation process, improving drilling efficiency and tool service life, and reducing costs.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of superhard material preparation, and in particular relates to a homogeneous pressure-transmitting pyrophyllite block and a preparation method thereof. Background Art
[0002] Polycrystalline diamond composite sheet is a composite material made of diamond powder and cemented carbide substrate sintered under ultra-high pressure and high temperature conditions. It has the high hardness, high wear resistance and thermal conductivity of diamond, and the strength and impact toughness of cemented carbide. It is an ideal material for manufacturing cutting tools, milling tools and other wear-resistant tools.
[0003] At present, with the gradual increase in market demand, the demand for oil and shale gas is gradually increasing. More and more oil and gas in deeper strata are being exploited. The complexity of the strata poses higher challenges to the drill teeth and higher requirements on the performance of the drill teeth. Improving the wear resistance, impact resistance and thermal stability of polycrystalline diamond composite sheets has become a major development direction of the superhard materials industry. The development of high-end polycrystalline diamond composite sheets will use a higher pressure platform. Higher pressure means higher sintering temperature and higher temperature increase, which is accompanied by an increase in the risk of blasting. Therefore, finding safe, reliable and high-pressure transmission efficiency talc blocks in the production process of polycrystalline diamond composite sheets has become a top priority.
[0004] Pyrophyllite powder briquette is a sealing pressure transmission medium for artificial diamonds. Pyrophyllite has good pressure transmission, sealing, electrical insulation, heat insulation and heat resistance, and good processing performance. However, due to the compressive resistance of minerals, when the synthetic pressure reaches the bearing pressure limit of the pyrophyllite sealing edge, a large production loss will occur. The use of existing pyrophyllite blocks, which are sealing pressure transmission media, cannot increase the internal pressure more effectively. China, with patent number CN201811532517.X, provides an external booster block. The pyrophyllite block is pressed and then baked to increase the cavity pressure. However, the external booster block of this patent will cause the overall compressible material to become less. At the same time, the pressing will cause the density of the upper and lower surfaces and the front, back, left and right surfaces of the pyrophyllite block to be different, which will cause differences in internal pressure transmission during use, and the risk of deformation and blasting of the top hammer will increase, resulting in increased hammer consumption.
[0005] Based on this, the present invention provides a talc pressure transmission block with uniform pressure transmission and high pressure transmission efficiency and a preparation method thereof, which can achieve the production of higher quality polycrystalline diamond composite sheets by increasing the internal pressure of the synthetic cavity, and reduce the chipping and tooth breakage of the drill teeth during the rotation process at the use end, which can greatly improve the drilling efficiency and the service life of the tool, and can also save costs. Summary of the invention
[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a homogeneous pressure-transmitting talc block and a preparation method thereof, which can improve the internal pressure of the synthesis cavity by optimizing the raw material composition and process, realize the production of higher quality polycrystalline diamond composite sheets, and reduce the chipping and tooth breakage of the drill teeth during the rotation process at the use end, which can greatly speed up the drilling efficiency and the service life of the tool, and also save costs.
[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0008] A method for preparing a homogeneous pressure-transmitting pyrophyllite block comprises the following steps:
[0009] 1) weighing pyrophyllite powders of different particle sizes and mixing them to obtain a mixed powder I; and uniformly mixing the mixed powder I with an additive to obtain a mixed powder II;
[0010] 2) Pre-pressing the mixed powder II, then demolding to obtain a pyrophyllite embryo, wrapping the pyrophyllite embryo, and then placing it in a cold isostatic press for cold isostatic pressing, and roasting the pyrophyllite embryo after the cold isostatic pressing to obtain the final product.
[0011] Furthermore, in step 1), the particle size of the pyrophyllite powder is in the range of 0.05-2.5 mm.
[0012] Specifically, in step 1), the pyrophyllite powders of different particle sizes include fine pyrophyllite powder with a particle size of 0.05-0.5 mm, medium pyrophyllite powder with a particle size of 0.5-2.0 mm, and large pyrophyllite powder with a particle size of 2.0-2.5 mm.
[0013] Furthermore, in the mixed powder I, the fine material pyrophyllite powder with a particle size of 0.05-0.5 mm accounts for 5-50% (mass fraction), the medium material pyrophyllite powder with a particle size of 0.5-2.0 mm accounts for 20-50% (mass fraction), and the large material pyrophyllite powder with a particle size of 2.0-2.5 mm accounts for 20-60% (mass fraction).
[0014] Furthermore, in step 1), the additive is one or two of water glass and porous magnesium oxide.
[0015] Furthermore, in step 1), the weight proportion of additives in the mixed powder II does not exceed 25%, and is more preferably 10-23%; further preferably, the weight proportion of porous magnesium oxide in the mixed powder II is between 0.1-20%.
[0016] Furthermore, in step 2), the pre-pressing is to load the mixed powder II into a hydraulic press mold and use a hydraulic press for pre-pressing.
[0017] Furthermore, in step 2), the pre-pressing pressure is 2-5 MPa, and the pre-pressing time is 30-100 s.
[0018] Furthermore, in step 2), when the talc embryo is wrapped, a cylindrical sleeve (the height shall not be higher than the height of the talc embryo) made of metal or alloy material (preferably stainless steel) is placed in the center of the embryo, and then the talc embryo and the sleeve are placed in a sealed bag made of polyester waterproof material (prepared from high-pressure polyethylene (LDPE) and high-pressure linear polyethylene, and its preparation method is not the inventive point of the present invention, so it will not be repeated), and the gaps in the sealed bag are filled with buffering materials such as pearl cotton, and the bag is vacuum-sealed.
[0019] Further, in step 2), the cold isostatic pressing treatment is specifically:
[0020] Using water as solvent, first add water to the container for cold isostatic pressing, then place the sealed bag containing the pyrophyllite embryo body into the container containing water, use the upper and lower pressure heads of the cold isostatic press to apply pressure to the water, so that the water acts on the sealed bag, the purpose is to generate isostatic pressure, the amount of water added is only enough to immerse the sealed bag containing the pyrophyllite embryo body in the water, and then maintain the pressure (at room temperature (25±5°C)) for a certain time under a certain pressure;
[0021] The equipment used in the cold isostatic pressing process is conventional equipment in the prior art, and its structure is not the inventive point of the present invention, so it will not be described in detail.
[0022] Furthermore, in step 2), during the cold isostatic pressing treatment, the pressure is 150-300 MPa and the holding time is 20-100 s.
[0023] Furthermore, in step 2), the roasting process step is to place the talc block body after cold isostatic pressing in a roasting furnace and adopt a segmented roasting method, which is to keep it at 300-350K for 3-12h, keep it at 400-475K for 4-10h, and keep it at 700-850K for 1-5h. The roasting process is normal pressure sintering.
[0024] The preparation method of the present invention improves the pressure transmission effect and the pressure transmission efficiency by adjusting the ratio of raw materials, adding additives such as water glass or porous magnesium oxide, changing the traditional pressing to a cold isostatic pressing method, and adopting a new roasting process, so as to make the sealing more stable and the pressure transmission more balanced.
[0025] The method prepares homogeneous pressure-transfer pyrophyllite blocks by mixing pyrophyllite powders of different particle sizes with additives, and then performing cold isostatic pressing and roasting.
[0026] Furthermore, the present invention also provides the use of the homogeneous pressure-transfer pyrophyllite block in the production of polycrystalline diamond compacts (PDC).
[0027] Furthermore, the present invention also provides a method for producing a polycrystalline diamond compact (PDC) using the homogeneous pressure-transmitting pyrophyllite block, comprising the following steps:
[0028] (1) mixing diamond micropowders of different particle sizes with binder micropowders to obtain mixed powder II;
[0029] (2) Put the mixed powder II and the cemented carbide into a shielding cup and seal it, and then place the assembled shielding cup into the pyrophyllite block prepared by the above method;
[0030] The assembled pyrophyllite blocks are placed in a six-sided top press for high temperature and high pressure sintering to obtain polycrystalline diamond composite PDC products.
[0031] Preferably, in step (1), the particle size of the diamond powder is in the range of 1 to 100 μm.
[0032] Preferably, in step (1), among the diamond micropowders of different particle sizes, the diamond micropowders with a particle size of 5-20 μm account for 30% to 40% (mass fraction), the diamond micropowders with a particle size of 20-50 μm account for 30% to 40% (mass fraction), and the diamond micropowders with a particle size of 50-100 μm account for 25% to 35% (mass fraction).
[0033] Preferably, in step (1), the binder powder is one or more of Co powder, Ni powder, Cr powder, W powder and WC powder, and no more than three kinds.
[0034] Preferably, in step (1), the mass proportion of the binder micropowder is 1-10% of the total mass of the diamond micropowder of different particle sizes and the binder micropowder.
[0035] Preferably, in step (2), the method for placing the mixed powder II and the cemented carbide (any one of the grades YG8\YG11\YG13) is as follows: the mixed powder II is placed in the lower shielding cup, the cemented carbide is placed in the upper shielding cup, and then the upper and lower shielding cups are buckled and sealed. The shielding cup is made of metal materials such as Ta, Nb, and Zr (the structure and preparation method of the shielding cup are not the inventive point of the present invention, so they will not be repeated).
[0036] Preferably, in step (2), during high temperature and high pressure sintering, the sintering temperature is 1450-1700°C, the pressure is 45-60MPa, the time for heating from room temperature (25±5°C) to the sintering temperature is 100-300s, the sintering heat preservation time is 150-500s, and the sintering temperature is reduced to room temperature (25±5°C) for about 120-360s.
[0037] The cold isostatic press used in the present invention is a conventional device in the prior art. The present invention utilizes it to implement cold isostatic pressing treatment. Its structure is not the inventive point of the present invention, so it will not be described in detail.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] 1. In the preparation method of the present invention, by adding porous magnesium oxide, the pressure transmission effect can be enhanced and the pressure transmission efficiency can be improved. At the same time, magnesium oxide can slow down the fluidity of pyrophyllite and enhance the sealing performance.
[0040] 2. The present invention increases the density of the pyrophyllite block, reduces the porosity, and improves the sealing effect at high temperature and high pressure by combining pyrophyllites of different particle sizes.
[0041] 3. The preparation method of the present invention uses cold isostatic pressing to press the pyrophyllite block, thereby ensuring that the pyrophyllite block shrinks in the same way in all directions and has the same density in all directions. When in use, the sealing of the block is more stable and the pressure transmission is more balanced.
[0042] 4. The preparation method of the present invention adopts a higher roasting temperature, which can remove more moisture from the raw materials, enhance the synthesis stability, reduce the risk of "blow-up", and at the same time reduce the operating pressure of the press equipment and extend its service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a photo of the impact test of polycrystalline diamond prepared in Comparative Example 1;
[0044] Figure 2 This is a photo of the impact test of the polycrystalline diamond prepared in Example 1;
[0045] Figure 3 This is a photo of the impact test of the polycrystalline diamond prepared in Example 2;
[0046] Figure 4 This is a photo of the impact test of the polycrystalline diamond prepared in Example 3. DETAILED DESCRIPTION
[0047] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Unless otherwise specified, the experimental methods used in the following examples and comparative examples are all conventional methods; the reagents, raw materials, etc. used in the following examples, unless otherwise specified, are all conventional commercially available products and can be obtained from commercial channels.
[0049] The cold isostatic press used in the following embodiments is a conventional device in the prior art. The present invention utilizes it to implement cold isostatic pressing treatment. Its structure is not the inventive point of the present invention, so it will not be described in detail.
[0050] Example 1
[0051] Embodiment 1 provides a method for preparing a homogeneous pressure-transmitting pyrophyllite block, and the specific steps are as follows:
[0052] 1) weighing pyrophyllite powders of different particle sizes and mixing them to obtain a mixed powder I, wherein the mixed powder I comprises 40% (mass fraction) of fine pyrophyllite powder with a particle size of 0.05-0.5 mm, 40% (mass fraction) of medium pyrophyllite powder with a particle size of 0.5-2.0 mm, and 20% (mass fraction) of large pyrophyllite powder with a particle size of 2.0-2.5 mm;
[0053] The mixed powder I is mixed with water glass to obtain a mixed powder II, wherein the water glass accounts for 15% of the total weight of the mixed powder II (the mixing in step 1) is carried out under normal temperature and pressure);
[0054] 2) The mixed powder II is loaded into a hydraulic press mold, and pre-pressed using a hydraulic press, with the pressure set to 3 MPa and the holding time being 40 seconds; then demoulding is performed to obtain a pyrophyllite embryo, and a stainless steel cylindrical sleeve is placed in the center of the embryo;
[0055] The pyrophyllite embryo and the sleeve are placed in a polyester waterproof material (prepared from high-pressure polyethylene (LDPE) and high-pressure linear polyethylene, the preparation method of which is not the invention point of the present invention, so it will not be repeated) sealed bag, the gap of the sealed bag is filled with cushioning materials such as pearl cotton, and air is evacuated to seal; then a cold isostatic pressing treatment is performed, specifically:
[0056] Using water as solvent, first add water to the container for cold isostatic pressing, then place the sealed bag containing the pyrophyllite embryo body into the container containing water, use the upper and lower pressure heads of the cold isostatic press to apply pressure to the water, so that the water acts on the sealed bag, the purpose is to generate isostatic pressure, the amount of water added is only enough to immerse the sealed bag containing the pyrophyllite embryo body in the water, and then set the pressure to 200MPa, and hold the pressure for 30s (room temperature (25±5℃)) for treatment;
[0057] The equipment used in the cold isostatic pressing process is conventional equipment in the prior art, and its structure is not the inventive point of the present invention, so it will not be described in detail;
[0058] The talc block body after cold isostatic pressing is calcined, and the specific process parameters are: first keep it at 320K for 5 hours, then keep it at 450K for 6 hours, and finally keep it at 800K for 3 hours. The calcination process is normal pressure sintering to obtain the final product.
[0059] Example 2
[0060] Embodiment 2 provides a method for preparing a homogeneous pressure-transmitting pyrophyllite block, and the specific steps are as follows:
[0061] 1) weighing pyrophyllite powders of different particle sizes and mixing them to obtain a mixed powder I, wherein the mixed powder I comprises 30% (mass fraction) of fine pyrophyllite powder with a particle size of 0.05-0.5 mm, 50% (mass fraction) of medium pyrophyllite powder with a particle size of 0.5-2.0 mm, and 20% (mass fraction) of large pyrophyllite powder with a particle size of 2.0-2.5 mm;
[0062] The mixed powder I is mixed with porous magnesium oxide to obtain a mixed powder II, wherein the porous magnesium oxide accounts for 10% of the total weight of the mixed powder II (the mixing in step 1) is carried out under normal temperature and pressure);
[0063] 2) The mixed powder II is loaded into a hydraulic press mold, and pre-pressed using a hydraulic press, with the pressure set to 3 MPa and the holding time being 40 seconds; then demoulding is performed to obtain a pyrophyllite embryo, and a stainless steel cylindrical sleeve is placed in the center of the embryo;
[0064] The pyrophyllite embryo and the sleeve are placed in a polyester waterproof material (prepared from high-pressure polyethylene (LDPE) and high-pressure linear polyethylene, the preparation method of which is not the invention point of the present invention, so it will not be repeated) sealed bag, the gap of the sealed bag is filled with cushioning materials such as pearl cotton, and air is evacuated to seal; then a cold isostatic pressing treatment is performed, specifically:
[0065] Using water as solvent, first add water to the container for cold isostatic pressing, then place the sealed bag containing the pyrophyllite embryo body into the container containing water, use the upper and lower pressure heads of the cold isostatic press to apply pressure to the water, so that the water acts on the sealed bag, the purpose is to generate isostatic pressure, the amount of water added is only enough to immerse the sealed bag containing the pyrophyllite embryo body in the water, and then set the pressure to 250MPa, and hold the pressure for 40s (room temperature (25±5℃)) for treatment;
[0066] The equipment used in the cold isostatic pressing process is conventional equipment in the prior art, and its structure is not the inventive point of the present invention, so it will not be described in detail;
[0067] The talc block body after cold isostatic pressing is calcined, and the specific process parameters are: first keep it at 340K for 10 hours, then keep it at 470K for 5 hours, and finally keep it at 820K for 2 hours. The calcination process is normal pressure sintering to obtain the final product.
[0068] Example 3
[0069] Embodiment 3 provides a method for preparing a homogeneous pressure-transmitting pyrophyllite block, and the specific steps are as follows:
[0070] 1) weighing pyrophyllite powders of different particle sizes and mixing them to obtain a mixed powder I, wherein the mixed powder I comprises 40% (mass fraction) of fine pyrophyllite powder with a particle size of 0.05-0.5 mm, 35% (mass fraction) of medium pyrophyllite powder with a particle size of 0.5-2.0 mm, and 25% (mass fraction) of large pyrophyllite powder with a particle size of 2.0-2.5 mm;
[0071] The mixed powder I is mixed with water glass and porous magnesium oxide to obtain a mixed powder II, wherein the water glass accounts for 8% of the total weight and the porous magnesium oxide accounts for 15% of the total weight (the mixing in step 1) is carried out under normal temperature and pressure);
[0072] 2) The mixed powder II is loaded into a hydraulic press mold, and pre-pressed using a hydraulic press, with the pressure set to 3 MPa and the holding time being 40 seconds; then demoulding is performed to obtain a pyrophyllite embryo, and a stainless steel cylindrical sleeve is placed in the center of the embryo;
[0073] The pyrophyllite embryo and the sleeve are placed in a polyester waterproof material (prepared from high-pressure polyethylene (LDPE) and high-pressure linear polyethylene, the preparation method of which is not the invention point of the present invention, so it will not be repeated) sealed bag, the gap of the sealed bag is filled with cushioning materials such as pearl cotton, and air is evacuated to seal; then a cold isostatic pressing treatment is performed, specifically:
[0074] Using water as a solvent, first add water to a container for cold isostatic pressing, then place a sealed bag containing a pyrophyllite embryo body into the container containing water, use the upper and lower pressure heads of the cold isostatic press to apply pressure to the water, so that the water acts on the sealed bag to generate isostatic pressure, and the amount of water added is only enough to immerse the sealed bag containing the pyrophyllite embryo body in the water, and then set the pressure to 180MPa and hold the pressure for 50s (room temperature (25±5°C)) for treatment;
[0075] The equipment used in the cold isostatic pressing process is conventional equipment in the prior art, and its structure is not the inventive point of the present invention, so it will not be described in detail;
[0076] The talc block body after cold isostatic pressing is calcined, and the specific process parameters are: first keep it at 300K for 8 hours, then keep it at 425K for 8 hours, and finally keep it at 750K for 4 hours. The calcination process is normal pressure sintering to obtain the final product.
[0077] By adjusting the pressure parameters of cold isostatic pressing and the temperature and holding time of roasting, the prepared pyrophyllite block can have different pressure transmission performance and physical properties to meet the needs of different application scenarios. In the actual production process, the process parameters can be adjusted according to specific needs to achieve the best effect.
[0078] Comparative Example 1
[0079] Comparative Example 1 did not use cold static pressing, but directly sintered after pressing, and the specific method was as follows:
[0080] 1) weighing pyrophyllite powders of different particle sizes and mixing them to obtain a mixed powder I, wherein the mixed powder I comprises 38% (mass fraction) of fine pyrophyllite powder with a particle size of 0.05-0.5 mm, 40% (mass fraction) of medium pyrophyllite powder with a particle size of 0.5-2.0 mm, and 22% (mass fraction) of large pyrophyllite powder with a particle size of 2.0-2.5 mm;
[0081] The mixed powder I is mixed with water glass to obtain a mixed powder II, wherein the water glass accounts for 15% of the total weight of the mixed powder II (the mixing in step 1) is carried out under normal temperature and pressure);
[0082] 2) The mixed powder II is loaded into a hydraulic press mold, and pre-pressed using a hydraulic press, with the pressure set to 8-10 MPa and the holding time being 40 seconds; then demoulding is performed to obtain a pyrophyllite embryo;
[0083] The pressed talc block is calcined, and the specific process parameters are: first, keep it at 320K for 3 hours, then keep it at 450K for 4 hours, and finally keep it at 800K for 1 hour. The calcination process is normal pressure sintering to obtain the final product.
[0084] Performance Test 1
[0085] The performance of the pyrophyllite blocks prepared in Examples 1 to 3 was tested, and Comparative Example 1 was used as a control. The test results are shown in Table 1.
[0086] Table 1
[0087]
[0088] It can be seen from Table 1 that after synthesis, the pyrophyllite blocks obtained in Examples 1 to 3 have a size range of less than 0.1 mm in front and back, left and right, and top and bottom. The overall pressure transmission is more uniform, and the sealing edge size range is reduced to 0.4 mm compared to the previous range fluctuation, and the sealing performance is better.
[0089] Performance test 1 mainly tests the pressure transmission efficiency and size to avoid the risk of "blow-ups".
[0090] Performance Test 2
[0091] The pyrophyllite blocks prepared in Examples 1 to 3 were used to prepare polycrystalline diamond, and performance tests were performed (wear resistance tests were performed according to the method in JB / T3235-2013 "Method for Determining Wear Ratio of Artificial Diamond Sintered Body"). Comparative Example 1 was used as a control, and the test results are shown in Table 2.
[0092] Specifically, the method for preparing a polycrystalline diamond compact (PDC) is as follows:
[0093] (1) diamond micropowders of different particle sizes are mixed with binder micropowders to obtain mixed powder II; the particle size range of the diamond micropowders is 1 to 100 μm; among the diamond micropowders of different particle sizes, the diamond micropowders of 5-20 μm particle size account for 35% (mass fraction), the diamond micropowders of 20-50 μm particle size account for 35% (mass fraction), and the diamond micropowders of 50-100 μm particle size account for 30% (mass fraction); the binder micropowders are Co powder, Ni powder, and WC powder. The proportions of the three binder micropowders can be conventionally prepared, and are not the inventive point of the present invention, so they will not be repeated; the mass proportion of the binder micropowders is 1-10% of the total mass of the diamond micropowders of different particle sizes and the binder micropowders;
[0094] (2) Put the mixed powder II into the lower shielding cup, put the cemented carbide (grade YG8) into the upper shielding cup, then buckle the upper and lower shielding cups and seal them. The shielding cup is made of metal materials such as Ta, Nb, and Zr (its structure and preparation method are not the inventive point of the present invention, so they will not be described in detail); put the assembled two shielding cups into the pyrophyllite block prepared in Example 1, 2 or 3;
[0095] The assembled pyrophyllite block is placed in a six-sided top press for high temperature and high pressure sintering (sintering temperature 1450-1700°C, pressure 45-60MPa, heating time from room temperature (25±5°C) to sintering temperature is 100-300s, sintering insulation time is 150-500s, and sintering temperature is reduced to room temperature (25±5°C) for about 120-360s. Other specific operating methods in the high temperature and high pressure sintering process of the PDC can be conventionally used in the prior art, and are not the inventive point of the present invention, so they are not described in detail) to obtain the corresponding PDC product.
[0096] Table 2
[0097] PDC Wear ratio (ten thousand) Comparative Example 1 1211 Example 1 1489 Example 2 1603 Comparative Example 3 1670
[0098] It can be seen from Table 2 that the polycrystalline diamond prepared by using the pyrophyllite blocks prepared in Examples 1 to 3 has a greater wear ratio, better wear resistance and a longer usable life.
[0099] Performance Test 3
[0100] The pyrophyllite blocks prepared in Examples 1 to 3 were used to prepare polycrystalline diamond. The preparation method was the same as that in Performance Test 2. The impact resistance test was performed. The impact resistance of the samples was tested using a CEAST9340 drop hammer impact tester. Comparative Example 1 was used as a control. The specific test method was as follows: a 40J energy was used to make the hammer fall freely, and the energy was used to impact the edges and corners of the sample for testing. The impact was stopped when microcracks appeared on the surface of the sample or serious damage occurred on the surface of the PCD. The number of impact resistances was obtained. The more times, the better the impact resistance. The test results are shown in Tables 3 and Figure 1 to Figure 4 As shown, Figure 1 to Figure 4 This is the damage morphology after impact.
[0101] Table 3
[0102] PDC Impact resistance level (times) Comparative Example 1 24 Example 1 36 Example 2 38 Comparative Example 3 40
[0103] It can be seen from Table 3 that the polycrystalline diamond prepared by using the pyrophyllite blocks prepared in Examples 1 to 3 has a higher impact resistance and a higher product bonding strength.
[0104] from Figure 1 to Figure 4 It can be seen that there are 3 tablet breakages in the comparative example; there is 1 tablet breakage in Example 1, and no tablet breakage is found in Examples 2 and 3.
[0105] The pyrophyllite block prepared by the present invention has the following functions in preparing polycrystalline diamond compact (PDC):
[0106] 1. Pressure transmission medium: In the process of ultra-high pressure diamond synthesis, pyrophyllite can transmit pressure evenly and efficiently due to its excellent hydrostatic properties, ensuring the smooth progress of the synthesis process.
[0107] 2. Sealing performance: Pyrophyllite has good sealing performance, which can prevent gas leakage under high temperature and high pressure and ensure the purity of the synthesis environment.
[0108] 3. Insulation: Pyrophyllite has high resistivity and can maintain electrical insulation under high temperature and high pressure, preventing current from passing through synthetic materials and affecting the synthetic quality of diamond.
[0109] 4. Heat resistance and thermal insulation: The low thermal conductivity of pyrophyllite gives it good thermal insulation performance at high temperatures, which helps maintain temperature stability during the synthesis process.
[0110] The above describes the specific implementation examples of the present invention. It should be understood that the present invention is not limited to the above specific implementation examples. Those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a homogeneous pressure-transmitting pyrophyllite block, characterized in that: The steps include: 1) Weighing pyrophyllite powders of different particle sizes and mixing them to obtain mixed powder I; uniformly mixing the mixed powder I with additives to obtain mixed powder II; 2) Pre-pressing the mixed powder II, and then demolding to obtain a pyrophyllite embryo, wrapping the pyrophyllite embryo, and then placing it in a cold isostatic press for cold isostatic pressing, and roasting the pyrophyllite embryo after cold isostatic pressing to obtain the final product.
2. The preparation method according to claim 1, characterized in that In step 1), the pyrophyllite powders of different particle sizes include fine pyrophyllite powder with a particle size of 0.05-0.5 mm, medium pyrophyllite powder with a particle size of 0.5-2.0 mm, and large pyrophyllite powder with a particle size of 2.0-2.5 mm.
3. The preparation method according to claim 2, characterized in that: In the mixed powder I, the fine material pyrophyllite powder with a particle size of 0.05-0.5mm accounts for 5-50wt%, the medium material pyrophyllite powder with a particle size of 0.5-2.0mm accounts for 20-50wt%, and the large material pyrophyllite powder with a particle size of 2.0-2.5mm accounts for 20-60wt%.
4. The preparation method according to claim 1, characterized in that: In step 1), the additive is one or two of water glass and porous magnesium oxide.
5. The preparation method according to claim 1, characterized in that: In step 1), the weight proportion of additives in the mixed powder II does not exceed 25%.
6. The preparation method according to claim 1, characterized in that: In step 2), the pre-pressing pressure is 2-5 MPa, and the pre-pressing time is 30-100 s.
7. The preparation method according to claim 1, characterized in that: In step 2), during the cold isostatic pressing treatment, the pressure is 150-300 MPa and the holding time is 20-100 s.
8. The preparation method according to claim 1, characterized in that: In step 2), the roasting process is to roast the talc block after cold isostatic pressing in stages, which are kept at 300-350K for 3-12h, kept at 400-475K for 4-10h, and kept at 700-850K for 1-5h.
9. The homogeneous pressure-transmitting pyrophyllite block prepared by the method according to any one of claims 1 to 8.
10. Use of the homogeneous pressure-transmitting pyrophyllite block according to claim 9 in the production of polycrystalline diamond composite sheets.
Citation Information
Patent Citations
Pyrophyllite block with high pressure transmission performance and making method of pyrophyllite block
CN109499482A